2018
DOI: 10.1093/eurpub/cky132
|View full text |Cite
|
Sign up to set email alerts
|

A long way to go: 20-year trends from multiple surveillance systems show a still huge use of tobacco in minors in Italy

Abstract: Policies enforced in Italy over the last 20 years slightly reduced ever smokers, but did not decrease current and daily smokers in 15-16-year-old adolescents, and determined an impact among younger adolescents. Stricter rules on youth tobacco access reduced ease of access to cigarettes, but did not affect adolescents' tobacco use. Stronger tobacco control measures are urgently needed in order to determine a steeper decline in smoking prevalence in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…[2] Among adolescents aged 15-16 years, current (past 30-day) smoking prevalence in Europe declined from 36% in 1999 to 22% in 2015a 35% reductionwith significant differences among countries: Finland, Sweden, and Ireland recorded a more than 50% decline, whereas Italy, Croatia, and Slovakia recorded a stalling or a slight decrease, from 37%-40% to 31%-37%. [3,4] In England, among 11-15 year old students, current smokers decreased from 17% in 1998 to 6% in 2016. [5] In the USA current smokers in high school students (commonly aged 14-18 years) declined from 15.8% in 2011 to 8.1% in 2018.…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Among adolescents aged 15-16 years, current (past 30-day) smoking prevalence in Europe declined from 36% in 1999 to 22% in 2015a 35% reductionwith significant differences among countries: Finland, Sweden, and Ireland recorded a more than 50% decline, whereas Italy, Croatia, and Slovakia recorded a stalling or a slight decrease, from 37%-40% to 31%-37%. [3,4] In England, among 11-15 year old students, current smokers decreased from 17% in 1998 to 6% in 2016. [5] In the USA current smokers in high school students (commonly aged 14-18 years) declined from 15.8% in 2011 to 8.1% in 2018.…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%
“…[8] In the USA, current users among high school students increased from 1.5% in 2011 to 11.7% in 2017, and even to 20.8% in 2018. [6] In Italy tobacco smoking among adolescents is still high and stalling in last decades (37% in [15][16] year old students; 23% in students aged 13-15 years in 2014-2015) [4]. Moreover, Italy has a regulatory environment on electronic cigarettes quite different from other countries [9,10]: up to 2014, electronic cigarettes were and are still sold as consumer products, no rules on their use in smoke-free public areas were implemented; advertising was allowed.…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%
“…Globally, 1 out of every 10 girls and 1 in every 5 boys aged 13–15 years use tobacco, with the highest smoking rates reported for the Western Pacific regions and Europe (World Health Organization [WHO], ). Findings from two surveys (2010 waves of the Health Behaviour in School‐Aged Children [HBSC] and the Global Youth Tobacco Surveillance [GYTS]) showed that, by the age of 15 years, over 50% of Italian adolescents had already experimented with tobacco products and that nearly 15% are daily smokers (Charrier et al., ; Gorini et al., ). Furthermore, data on susceptibility to initiate smoking within one year among those who had not yet tried indicate that about 40% of never smokers fell into the “susceptible” category in 2010, which decreased to 33.4% in 2014 (Charrier, Berchialla, & Gruppo HBSC Italia ; Global Youth Tobacco Surveillance, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions were drawn in an evaluation of the WHO's MPOWER measures to reduce smoking‐related deaths, with 88 countries having adopted at least one of the six measures, for which increased cigarette taxes and comprehensive smoke‐free laws were estimated to have averted over 5 million smoking‐attributable deaths (Levy et al ., ). On the other hand, as an example of outstanding challenges, tobacco surveillance in Italian minors over the past 20 years has shown only modest success in reduction in smoking prevalence, with declines in 11‐ to 13‐year‐olds but no decline in current and even an increase in daily smokers among 15‐ to 16‐year‐olds (Gorini et al ., ), illustrating the need for stronger tobacco control measures in adolescents.…”
Section: Barriers To Overcome In Primary Prevention Of Cancermentioning
confidence: 99%